PEMANFAATAN BUKU KIA OLEH IBU HAMIL DALAM UPAYA PENCEGAHAN KOMPLIKASI KEHAMILAN DI PUSKESMAS MURUNG PUDAK - Yani, Anggeri; Suhartati, Susanti; Rizali, Muhammad (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Every day there are 830 women die from preventable causes related to pregnancy and childbirth. The preliminary study found 21 pregnant women with complications, there were 10 pregnant women who did not know how to overcome pregnancy complications and there were 11 pregnant women who did not understand what to do in the event of an obstetric emergency, even though it was all in the MCH book they had. The purpose of the study was to determine the use of maternal and child health books (MCH) by pregnant women in an effort to prevent pregnancy complications at the Murung Pudak Health Center in 2022. This research method is with descriptive-analytical methods. The design or design used in this study is a cross-sectional study research design. The results of the research in the category of Maternal Knowledge About the Utilization of MCH Books were obtained from 37 respondents, 34 respondents (91.9%) with the Good Category, 3 respondents (8.1%) with the Sufficient Category while the less category did not exist in terms of knowledge of the use of MCH books in efforts to prevent pregnancy complications.